Moving from idea to reality: The barriers and enablers to implementing Child and Family Hubs policy into practice in NSW, Australia - Anna Calik; Huei Ming Liu; Alicia Montgomery; Suzy Honisett; Kerri-Anne Van Munster; Tamara Morris; Valsamma Eapen; Sharon Goldfeld; Harriet Hiscock; John Eastwood; Susan Woolfenden (BMC, 2024)
Abstract Background Adverse childhood experiences can impact physical and mental health throughout the lifespan. To support families experiencing adversity and improve child health and developmental equity, an integrated, multi-sector response is required. Child and Family Hubs (Hubs) are a feasible and acceptable approach to providing such a response. In the Australian context, a number of federal and New South Wales (NSW) state policies support an integrated, multi-sector response using Hubs to support families experiencing adversity. This study examined NSW policy stakeholder and health service manager perspectives on the barriers and enablers to translating policy into practice in the implementation of Child and Family Hubs. Methods Semi-structured interviews were conducted with 11 NSW government policy stakeholders and 13 community health service managers working in child and family policy and planning or child and family community-based services. Interviews were of 30-60 min duration and explored stakeholder knowledge, perspectives and experiences around childhood adversity, and barriers and enablers to operationalizing policies supporting Hubs. Analysis of barriers and facilitators to implementation of Hub models of care was undertaken using the Consolidated Framework for Implementation Research (CFIR). Results Key barriers that emerged included short-term and inconsistent funding, lack of resourcing for a Hub co-ordinator, limited support for evaluation and insufficient time to plan for Hub implementation. Key enablers included flexibility and adaptability of Hub models to meet local needs, formal change management processes, strong governance structures and engagement among Hub practitioners. Key insights included the importance of targeted strategies to support sustained individual practice change and the need for organization-wide commitment to enable the successful adoption and maintenance of the Hub model of care. Conclusions This study provides valuable insights and contributes evidence around what is needed to strengthen and support the operationalization and scalability of the Hub model of care. Key recommendations for Hub practitioners include the importance of formal change management processes and establishment of strong governance structures, while key recommendations for policymakers include the need for sustainable Hub funding and a standardized, evidence-based framework to support Hub implementation and evaluation.